Unraveling the neurotoxicity of titanium dioxide nanoparticles: focusing on molecular mechanisms - Song, Bin; Zhang, Yanli; Liu, Jia; Feng, Xiaoli; Zhou, Ting; Shao, Longquan (Beilstein Journal of Nanotechnology, 2016)
Titanium dioxide nanoparticles (TiO2 NPs) possess unique characteristics and are widely used in many fields. Numerous in vivo studies, exposing experimental animals to these NPs through systematic administration, have suggested that TiO2 NPs can accumulate in the brain and induce brain dysfunction. Nevertheless, the exact mechanisms underlying the neurotoxicity of TiO2 NPs remain unclear. However, we have concluded from previous studies that these mechanisms mainly consist of oxidative stress (OS), apoptosis, inflammatory response, genotoxicity, and direct impairment of cell components. Meanwhile, other factors such as disturbed distributions of trace elements, disrupted signaling pathways, dysregulated neurotransmitters and synaptic plasticity have also been shown to contribute to neurotoxicity of TiO2 NPs. Recently, studies on autophagy and DNA methylation have shed some light on possible mechanisms of nanotoxicity. Therefore, we offer a new perspective that autophagy and DNA methylation could contribute to neurotoxicity of TiO2 NPs. Undoubtedly, more studies are needed to test this idea in the future. In short, to fully understand the health threats posed by TiO2 NPs and to improve the bio-safety of TiO2 NPs-based products, the neurotoxicity of TiO2 NPs must be investigated comprehensively through studying every possible molecular mechanism.
Keywords: autophagy; brain; DNA methylation; neurotoxicity; titanium dioxide nanoparticles